POLITICS OF RECOGNITION: A RELATIONSHIP BETWEEN ORANG LOM AND STATE FOR CIVIL RIGHTS SERVICES (STUDY IN AIR ABIK, BELINYU DISTRICT, BANGKA BELITUNG ISLANDS) - Bahjatul Murtasidin; Michael Jeffri Sinabutar; Bob Morison Sigalingging (Berumpun: International Journal of Social, Politics, and Humanities, 2021)
Adherents of ancestral religions stand in two entities as indigenous peoples and as citizens after the Constitutional Court Decision Number 96 of 2016 provided hope for believers as citizens to express their communal identity. This research aims to find out the form of relationship between Orang Lom and the state to civil rights services and to see the efforts made by Orang Lom to gain recognition from the state so that they have access to civil services. The approach in this study put forward Axel Honneth's political theory of recognition by dissecting it through the elements of subjectivity, objectivity, and solidarity that developed in the practice of civil rights services for the Mapur Lom Tribe. This study utilized a descriptive qualitative method with a case-study approach in the Mapur Indigenous Community of Orang Lom, Belinyu District, Bangka Belitung. The data collection technique was conducted through observation, in-depth interviews, and literature studies. Moreover, data analysis applied various sources, both from key informants and secondary data. The data analysis was performed by using an interactive model in the form of data reduction, data presentation, and conclusion. The results showed that the relationship between Orang Lom and the state seemed more administrative in nature on the basis of the prevailing laws and regulations regarding civil service and population administration. At this time, Orang Lom can put their belief in God Almighty in the column of National ID Card, but traditional marriage has not been recognized so that it has an impact on children's birth certificates and education services. In terms of the funeral of the adherents of folk religions, they do not receive any rejection from the community while for the organization's administration, the existence of the Mapur Customary Institution of Orang Lom receives recognition from Majelis Luhur Kepercayaan Indonesia.